2019
DOI: 10.1177/0009922819863665
|View full text |Cite
|
Sign up to set email alerts
|

Study of Caregivers Regarding Pediatric Poisoning

Abstract: The overall objective was to characterize action by caregivers when a potential poison exposure occurs and identify barriers to poison control center (PCC) utilization. A prospective survey of caregivers of pediatric patients who presented to an emergency department for a potential poison exposure was completed by each study participant. A total of 371 surveys were completed between August 2016 and August 2017. The majority of patients were 3 years or younger. Caucasians were more likely to have heard of the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…Similarly, in a survey conducted in the same children's hospital as our study, over 60% of patients with government-sponsored insurance felt the PCC reports exposures to authorities compared with 42% with private insurance. 19 Notably, this study found that government-sponsored insurance was a significant predictor of ED self-referral, confirming the trends found in previous investigations. Improving patient education and self-efficacy regarding PCC utilization across populations of varying racial and insurance demographics may help curb barriers to access.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, in a survey conducted in the same children's hospital as our study, over 60% of patients with government-sponsored insurance felt the PCC reports exposures to authorities compared with 42% with private insurance. 19 Notably, this study found that government-sponsored insurance was a significant predictor of ED self-referral, confirming the trends found in previous investigations. Improving patient education and self-efficacy regarding PCC utilization across populations of varying racial and insurance demographics may help curb barriers to access.…”
Section: Discussionsupporting
confidence: 91%
“…Among women attending a women, infants, and children clinic, Kelly and Groff 8 found that there was substantially less familiarity with PCC services and more hesitation with its utilization due to possible accusations of neglect. Similarly, in a survey conducted in the same children's hospital as our study, over 60% of patients with government-sponsored insurance felt the PCC reports exposures to authorities compared with 42% with private insurance 19 . Notably, this study found that government-sponsored insurance was a significant predictor of ED self-referral, confirming the trends found in previous investigations.…”
Section: Discussionsupporting
confidence: 91%
“…The current study also was limited to eleven years of data since specific age groups of childhood poisoning cases have only been available since 2009. Finally, there is increasing usage of the internet and social media platforms for readily available information on topics related to poison exposures [ 16 ]. This could be a contributing factor to the declining trend in reported cases in NPDS.…”
Section: Discussionmentioning
confidence: 99%
“…Take-back programs are also in existence to safely dispose of medications when prescriptions are completed or outdated [ 14 ]. The most promising educational interventions targeting parents include home safety education for safe storage of medicines [ 15 ] and cleaning products and accessibility of the telephone number for Poison Control Centers (PCCs) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%